KONSERVASI ARSITEKTUR RUMOH ACEH - Azhar Abdullah Arif (Talenta Publisher, 2018)
Maintain the authenticity and identity of Architecture Rumoh Aceh, the mandate entrusted by its predecessor, the founder utoh or buildings in Aceh for the next generation of Acehnese society, especially who work as experts and historians and cultural buildings. Study Rumoh Aceh can be initiated from the treasury of the culture and customs of Aceh in the past, and continued with tectonic culture that blends the building's existence Rumoh Aceh that we know today. But if not maintained and conservation efforts then gradually Rumoh Aceh will increasingly disappear in Aceh. This is due to the less proficient Utoh building Rumoh Aceh and understand the philosophy and the building process. Rumoh Aceh is Aceh cultural treasures that can still be found in some areas in Aceh Province, among others in the region Lubok Gampong Aceh Besar district. Where there are several buildings Rumoh Aceh are well maintained. However, due to the growing need for space and residential facilities increasingly complex caused the changes and additions to the original building parts. This led to the decreasing number of Rumoh Aceh remaining. So that the necessary effort to organize the village area and an assessment of the suitability of the original typology Rumoh Aceh. Lubok gampong region is an area of the township near the city of Banda Aceh, making it easier to conduct visual observation of the phenomenon of change in residential building typology Rumoh Aceh in the region. The study involved several students who study subjects Architectural Conservation to record symptoms of the changes. Additionally the Aceh provincial government also has set Gampong Lubok as about culture village area periodically ceremonies by presenting the tourists at home and abroad. This is in accordance with the Aceh as Halal Cultural Tourism Destination.